2018
DOI: 10.11124/jbisrir-2017-003486
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transitional care programs on health services utilization in community-dwelling older adults: a systematic review

Abstract: Based on a review of 23 studies conducted in the USA, Hong Kong, Canada, Germany, the Netherlands, Sweden and Switzerland, we identified four major conclusions. First, transitional care reduces rehospitalization rates over time, with the largest effects seen at 30 days. Second, transitional care may increase the utilization of primary care services and thus have a favourable impact on preventative care. Third, transitional care may reduce home health usage. Fourth, transitional care interventions of one month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 37 publications
0
51
0
1
Order By: Relevance
“…There is very little evidence regarding why certain transitional care interventions work in some settings or contexts but not in others [ 76 ]. This approach enables a focus on the complexity of interactions among the many contextual, macro-level factors that can affect implementation, which have been noted as highly relevant in determining both the outcomes and scalability of transitional care interventions [ 8 , 28 , 29 ]. Second, the study will include a cost analysis from a societal perspective – an outcome that has been overlooked in previous transitional care studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is very little evidence regarding why certain transitional care interventions work in some settings or contexts but not in others [ 76 ]. This approach enables a focus on the complexity of interactions among the many contextual, macro-level factors that can affect implementation, which have been noted as highly relevant in determining both the outcomes and scalability of transitional care interventions [ 8 , 28 , 29 ]. Second, the study will include a cost analysis from a societal perspective – an outcome that has been overlooked in previous transitional care studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is an inherent limitation of pragmatic trials [ 78 , 79 ], and is also a common challenge associated with transitional care evaluations. Variation in the nature and scope of interventions across settings has led authors of multiple systematic reviews to qualify their conclusions about the efficacy of transitional care models [ 27 29 , 35 ]. Close monitoring throughout the duration of the study will assist the investigators in determining any adaptations that need to be made to the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies have shown that there are often adverse events after discharge, as medication errors, use of emergency services and hospital readmissions. [2][3] Thus, efforts are necessary to ensure care continuity at home.…”
mentioning
confidence: 99%
“…4 This is an important strategy to ensure the integral care during hospitalization and after hospital discharge, increasing the use of primary care services and reducing hospital readmissions. [3][4][5][6] The literature shows that the nurse has been one of the professionals most involved in care transition from the hospital to the domicile, developing activities in the care planning for discharge, aid for social rehabilitation, health education, articulation with other health services and post-discharge follow-up. [7][8][9] The nurse allows hospitalization to become a moment of learning, with an exchange of knowledge among patient, family and healthcare professional.…”
mentioning
confidence: 99%